The Effectiveness of UK DMO Websites Perceived by Chinese International Students - Dong, Yuan (2008)
Destination Marketing Organizations (DMOs) are in charge of destination marketing and management and has adopted website as an important market communication channel. It can be considered as a medium that enable DMOs to promote their destination effectively and attract customersâ attention. With the increasing investment in DMOs website, the effectiveness of DMO websites has drawn considerably attentions. With more than 50000 Chinese students coming to the UK to study every year, Chinese international students market is a significant market segment with tremendous profit. Besides, most of the Chinese students are coming from the middle class families; they have both the ability to spend money on travelling and the time to travel. As an international student without extensive knowledge about UK, tourism website and brochure are becoming the most frequent and easiest way to plan for holiday. It contains important sources of information for tourists and can be assumed that they influence the Chinese studentsâ choices. This study aims to examine the effectiveness of DMOs websites perceived by Chinese international students. Through the investigation of three different UK DMOs websites, this study will address the needs and requirements of DMOs websites at different levels (country, region and city) in terms of information content, operational functions and service functions, further identify the gap between the needs of tourists and the information and services provided by the websites. Moreover, the behaviours and attitudes of Chinese international students after visiting the DMOs websites will be identified in order to find out the impact and influnce of DMOs websites on their awareness, motivations and satisfactions. Suggestions will be provided to ameliorate the situation according to the result of the research.